2006
DOI: 10.7202/013975ar
|View full text |Cite
|
Sign up to set email alerts
|

The role of antibiosis in the antagonism of different bacteria towards Helminthosporium solani, the causal agent of potato silver scurf

Abstract: RésuméDes antagonistes bactériens enversHelminthosporium solaniont été soumis à différents essais en vue de déterminer le rôle de l'antibiose dans l'antagonisme observé. Parmi les souches bactériennes évaluées, sept (Alcaligenes piechaudii, Aquaspirillum autotrophicum, Cellulomonas fimi, Pseudomonas chlororaphis, Pseudomonas putida(souches 94-19 et E-30) etStreptomyces griseus) ont produit dans le … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…This clearly suggested that antibiosis is an important contributor to the antagonistic effect of these bacteria through the diffusion of antifungal compounds into the medium. In confrontation with the present finding, Martinez et al [18] reported that plates containing exudates of precultured A. piechaudii, P. chlororaphis and S. griseus inhibited both mycelial growth and conidiation of Helminthosporium solani. Moreover, implication of diffusible bioactive metabolites such as phenazine, pyoluteorin, pyrrolnitrin and cyclic lipopeptides in antagonism is well documented [14].…”
Section: Assessment Of Inhibitory Traitssupporting
confidence: 76%
See 1 more Smart Citation
“…This clearly suggested that antibiosis is an important contributor to the antagonistic effect of these bacteria through the diffusion of antifungal compounds into the medium. In confrontation with the present finding, Martinez et al [18] reported that plates containing exudates of precultured A. piechaudii, P. chlororaphis and S. griseus inhibited both mycelial growth and conidiation of Helminthosporium solani. Moreover, implication of diffusible bioactive metabolites such as phenazine, pyoluteorin, pyrrolnitrin and cyclic lipopeptides in antagonism is well documented [14].…”
Section: Assessment Of Inhibitory Traitssupporting
confidence: 76%
“…This may be attributed to the fact that broth-based environment allowed a synergistic expression of all the mechanisms involved in biocontrol from all the interacting sites. Concomitantly, variable responses in reduction in fungal biomass in broth culture as compared to dual plate assay have been reported as certain antifungal metabolites are induced or repressed by the absence or presence of pathogen [18]. In a similar study, Kumari and Khanna [16] reported 11.6-62.97% reduction in proliferation of F. oxysporum by Bacillus sp.…”
Section: Assessment Of Inhibitory Traitsmentioning
confidence: 98%
“…The mechanisms which Pseudomonas use for effective biocontrol include direct antagonism, production of several metabolites with antimicrobial activity toward fungi and cell wall degrading enzymes (Haas and Keel 2003). Pseudomonas chlororaphis had previously been shown to produce antibiotics (Assis et al 1998;Chin-A-Woeng et al 1998), inhibited both mycelial growth and conidial germination of Helminthosporium solani (Martinez et al 2006) and also improved wheat growth under field conditions (Carlier et al 2008). In our previous work P. chlororaphis TSAU 13 had antagonistic effect on several pathogenic fungi such as F. oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 96%
“…Elad & Shtienberg (15) e Koné et al (18) observaram a presença de bactérias, actinobactérias e leveduras nos extratos aquosos supressivos e a perda da eficácia da supressividade sob microfiltração ou autoclavagem. A ação dos microrganismos presentes em extratos aquosos sobre a germinação de conídios de fungos pode estar associada à produção de sideróforos (14), metabólitos voláteis (21) e ou pelo mecanismo de antibiose (22). Todos os extratos aquosos e os materiais orgânicos, independentemente da autoclavagem, na concentração de 5% promoveram o crescimento micelial do patógeno (Tabelas 2, 3, 4).…”
Section: Discussão Dos Resultadosunclassified